An Analysis of Mass Casualty Incidents in the Setting of Mass Gatherings and Special Events. (16th April 2014) - Turris, Sheila A.; Lund, Adam; Bowles, Ronald R.
Abstract Objectives Mass gatherings (MGs) and special events typically involve large numbers of people in unfamiliar settings, potentially creating unpredictable situations. To assess the information available to guide emergency services and onsite medical teams in planning and preparing for potential mass casualty incidents (MCIs), we analyzed the literature for the past 30 years. Methods A search of the literature for MCIs at MGs from 1982 to 2012 was conducted and analyzed. Results Of the 290 MCIs included in this study, the most frequently reported mechanism of injury involved the movement of people under crowded conditions (162; 55.9%), followed by special hazards (eg, airplane crashes, pyrotechnic displays, car crashes, boat collisions: 57; 19.6%), structural failures (eg, building code violations, balcony collapses: 38; 13.1%), deliberate events (26; 9%), and toxic exposures (7; 2.4%). Incidents occurred in Asia (71; 24%), Europe (69; 24%), Africa (48; 17%), North America (48; 27%), South America (27; 9%), the Middle East (25; 9%), and Australasia (2; 1%). A minimum of 12 877 deaths and 27 184 injuries resulted. Conclusions Based on our findings, we recommend that a centralized database be created. With this database, researchers can further develop evidence to guide prevention efforts and mitigate the effects of MCIs during MGs. (Disaster Med Public Health Preparedness. 2014;0:1-7)